Chemistry acids, bases, and salts (St. Louis : Coronet Films & Video)
Described acids, bases and salts - three related groups of compounds, all electrolytes with great significance to our industrial world and to life itself
Copy available in DVD format
Executive producer, Ellica Rowen ; script, Douglas L. Lieberman, Mel Waskin
Keywords: Acids; Bases (Chemistry).; Salts